Solar-Powered smart irrigation and fertilization with loRa remote monitoring - Santi Febri Arianti; Antonius Antonius; Daniel Simbolon; Edwinner Lamboris Sitorus; Erdianto Parluhutan Sitorus (Journal of Intelligent Decision Support System (IDSS), 2023)
Efficient water management is a critical challenge in agriculture, particularly in rural areas where water resources may be scarce. To address this issue, this research introduces and assesses a solar-powered automatic drip irrigation system with a fertilization feature, specifically tailored for chili farming in the rural community of Banua Huta village. The system incorporates LoRa technology for remote monitoring, allowing farmers to efficiently manage water use and nutrient application. The study focused on evaluating the system's performance concerning water conservation, fertilizer application, and crop productivity. The results demonstrated a substantial improvement in irrigation efficiency, with water usage reduced by 33.5% compared to conventional methods. The fertilization feature of the system not only facilitated targeted nutrient delivery but also resulted in increased crop growth rates of up to 30% and improved leaf health by up to 35%. This innovative solar-powered automatic drip irrigation system showcases a practical and sustainable approach to water and nutrient management in rural agriculture, demonstrating its potential for widespread adoption in similar settings.